POLIO ERADICATION IN PAKISTAN: NOT AS FAR AS IT SEEMS - Wadood, Mufti Zubair (Journal of Postgraduate Medical Institute, 2015)
Since its inception in 1994, Pakistan's polio eradicationprogram has made significant strides towardsachieving the goal of polio eradication1. This is evidentfrom a 99% reduction in the number of polio cases andrestriction of wild poliovirus (WPV) circulation to fewergeographical areas. However, from the global perspectiveas well as in view of the initial timeline set for polioeradication (year 2000), Pakistan currently stands thefarthest from the goal. In fact, Pakistan is currently consideredto be the single largest threat to global polioeradication.